Critical interventions of old students’ associations for secondary school welfare in Oyo state, Nigeria (2023)
Stakeholders in educational institutions like business organisations, parent teachers’ association and old students’ association have been encouraged by governments to participate in the development of schools in Nigeria. The old students’ associations’ interventions, especially, in the south western Nigeria are widespread but the interventions are not well documented and guided by government policies. This paper identified few organised old students’ associations in Oyo state, Nigeria and it examined the contributions they have made to the welfare of secondary schools. Findings showed that building of classrooms, supply of school equipment, donation of laboratory facilities, scholarship and awards are areas of intervention that old students' associations have made most impacts in Oyo State, Nigeria.